Biología reproductiva de Hypophthalmus edentatus (Spix & Agassiz, 1829) "maparate" y Plagioscion squamosissimus (Heckel, 1840) "corvina" en el Bajo Amazonas, Caballococha, Loreto - Perú, 2020 - Pizuri Chino, Erwin Karin José (2022)
The present work had the purpose of studying the reproductive biology of Hypophthalmus edentatus (Spix & Agassiz, 1829) "maparate" and Plagioscion squamosissimus (Heckel, 1840) "corvina" in the lower Amazon, Caballococha, Loreto - Peru, during the period from November 2020 to October 2021, 240 specimens of Hypophthalmus edentatus and 355 specimens of Plagioscion squamosissimus were collected, the biological samples of the fish under study, gonads, stomachs, livers, otoliths, stomach contents, were obtained from the market, from fishing landings in the city of Caballococha and products of exploratory fishing. A total of 240 maparates and 355 corvinas were analyzed for a period of 12 months, collecting the information in the early hours of the day (05:00 to 11:00 hours). Samples were processed in a market area equipped with dissection and biometric instruments, biometrics (length and weight) were taken for both species, and gonad maturation was identified by direct visual observation. In the lower basin of the Amazon River, the maparate presents its first size of sexual maturity at 25.7 cm in females, and 29.4 cm in males, of standard length. On the other hand, the croaker presents a size of first sexual maturity at 28.8 cm in females, and 26.5 cm in males, of standard length. The sexual ratio was higher for the females in relation to the males of maparate, it obtained 3:1, and in croaker it was obtained 1:1. The gonadosomatic index was high 1.2% for maparate and 2.49% for meager.